Pengembangan Media Pembelajaran Berbasis Virtual Reality Pada Mata Kuliah Anatomi Dan fisiologi Manusia Pada Mahasiswa Semester VI Pendidikan Biologi - Ahmad Khuzeir Tarmizi; Haning Hasbiyati; Miftahul Hakim (Pendidikan Biologi,Universitas Islam Jember, 2020)
The development of learning media based on virtual reality aims to determine the feasibility of this media in learning. This media is validated by two experts, namely material experts and media experts. During the validation of the media material expert, he received an assessment percentage of 79.8% and in his testing the media expert validation received a percentage of 96.8%, which means that the test is very valid. The sample trial was 9 people, got a percentage score of 74.6% (very feasible), while during the implementation trial there were about 19 people who got a percentage score of 79.2 (very feasible). From these trials it can be concluded that virtual reality learning media is very feasible and can be implemented into the real learning process.Keywords: Human Anatomy and Physiology, learning media, VR